Tingkat Pengetahuan Suami tentang Pentingnya Peran dan Dukungannya kepada Istri selama Masa Kehamilan, Persalinan dan Masa Nifas di Duren Mekar Depok - Sari, Marlynda Happy Nurmalita; Ramadanti, Sopie (Journal of Religion and Public Health, 2020)
The adaptation of women to become mothers requires the support of their husbands and those around them. Husband's support is an easy way to overcome anxiety during pregnancy, reduce labor pain and postpartum depression in the wife. This study aims to determine the husband's level of knowledge about the importance of his role and support for his wife during pregnancy, childbirth and the puerperium both from predisposing factors, supporting factors and driving factors in Kampung Desa RT 003 RW 01 Duren Mekar Depok in 2018. This research is descriptive. with a cross sectional design and the type of data taken is primary data using a questionnaire then the results are processed by the stages of data selection, data tabulation, and percentage calculations which are then presented in a frequency distribution table. While the respondents who were taken were men from couples of childbearing age who already have children who live in the Kampung Desa environment RT 003 RW 01 Duren Mekar with a sample of 34 respondents from a total population of 52 respondents. From the results of the study, it was found that 32 respondents (94.1%) had a good level of knowledge, as many as 28 respondents (100%) of 28 respondents with a high level of education had a good level of knowledge, as many as 27 respondents (93.1%) from 29 respondents who received information from health workers had a good level of knowledge, as many as 32 respondents (94.1%) of 34 respondents who had a working status when their wives were pregnant until postpartum had a good level of knowledge, as many as 16 respondents (94.1% ) of 17 respondents who fall into the category of late adulthood (36-45 years) have a good level of knowledge. It is hoped that further research will allow researchers to examine more and more extensive other variables that affect the husband's level of knowledge about the importance of his role and support for his wife during pregnancy until the postpartum period.Keywords: knowledge, education, sources of information, occupation, age.Abstrak Adaptasi perempuan menjadi seorang ibu, memerlukan dukungan suami dan orang disekitarnya. Dukungan suami merupakan cara mudah untuk mengatasi kecemasan masa kehamilan, mengurangi nyeri persalinan serta depresi postpartum pada istri. Penelitian ini bertujuan untuk mengetahui tingkat pengetahuan suami tentang pentingnya peran dan dukungannya kepada istri selama masa kehamilan, persalinan dan masa nifas baik dari faktor predisposisi, faktor pendukung maupun faktor pendorong di Kampung Desa Duren Mekar Depok tahun 2018. Penelitian ini bersifat deskriptif dengan rancangan cross sectional dan jenis data yang diambil adalah data primer dengan menggunakan kuesioner kemudian hasilnya diolah dengan tahap seleksi data, tabulasi data, dan perhitungan persentase yang selanjutnya disajikan dalam tabel distribusi frekuensi. Sedangkan responden yang diambil adalah laki – laki dari pasangan usia subur yang sudah memiliki anak yang tinggal di lingkungan Kampung Desa RT 003 RW 01 Duren Mekar dengan jumlah sampel 34 responden dari jumlah populasi 52 responden. Dari hasil penelitian didapatkan sebesar 32 responden(94,1%) memiliki tingkat pengetahuan yang baik, sebanyak 28 responden (100%) dari 28 responden dengan tingkat pendidikan yang tinggi memiliki tingkat pengetahuan yang baik, sebanyak 27 responden (93,1%) dari 29 responden yang mendapatkan sumber informasi dari tenaga kesehatan memiliki tingkat pengetahuan yang baik, sebanyak 32 responden (94,1%) dari 34 responden yang memiliki status bekerja saat istrinya hamil sampai nifas memiliki tingkat pengetahuan yang baik, sebanyak 16 responden (94,1%) dari 17 responden yang masuk dalam kategori dewasa akhir (36-45 tahun) memiliki tingkat pengetahuan yang baik. Penelitian selanjutnya diharapkan agar peneliti dapat meneliti variabel – variabel lain yang lebih banyak dan lebih luas yang mempengaruhi tingkat pengetahuan suami tentang pentingnya peran dan dukungannya kepada istri selama masa kehamilan sampai nifas.Kata kunci : pengetahuan, pendidikan, sumber informasi, pekerjaan, usia.